Stress Levels and Coping Strategies among Nursing Students: A Study from Selected Colleges in Bangladesh - Madhu, Sajib; Omi, Fardina Rahman; Salam, M. Abdus; Islam, Md Sakibul (Diversity: Disease Preventive of Research Integrity, 2025)
Stress among nursing students has been widely recognized as a persistent challenge, yet there remains a gap in understanding the interplay between stressors and coping mechanisms within the South Asian context, particularly Bangladesh. This study aimed to assess stress and coping strategies among diploma nursing and midwifery students in Bangladesh. A cross-sectional study was conducted among 300 students from selected nursing colleges, using a semi-structured, self-administered questionnaire. Stress was measured with the Perceived Stress Scale (PSS), while coping strategies were assessed with the Coping Behavior Inventory (CBI). The results showed that students reported moderate levels of stress, with assignments and workload (1.84±0.70) being the most prominent stressors, followed by peers and daily life (1.77±0.79), clinical environment (1.68±0.88), teachers and nursing staff (1.38±0.78), and taking care of patients (1.32±0.64), while lack of professional knowledge and skills was the least reported (1.27±0.79). The most frequently used coping strategy was problem solving (2.82±0.69), followed by optimism (2.65±0.67), transference (2.59±0.73), and avoidance (1.35±0.79). A significant mild positive correlation was found between stress and coping strategies (r = 0.229, p = 0.000), while avoidance coping was positively associated with all stress domains. These findings suggest that although nursing students face substantial stress, they often adopt constructive coping strategies, particularly problem solving and optimism, which should be reinforced through structured stress management and resilience-building programs in nursing education.